Stress-Related Alcohol Consumption in Heavy Drinkers Correlates with Expression of miR-10a, miR-21, and Components of the TAR-RNA-Binding Protein-Associated Complex - Beech, Robert D.; Leffert, Janine J.; Lin, Aiping; Hong, Kwangik A.; Hansen, Julie; Umlauf, Sheila; Mane, Shrikant; Zhao, Hongyu; Sinha, Rajita (Alcoholism, clinical and experimental research, 2014)
Background Alterations in stress‐related gene expression may play a role in stress‐related drinking and the risk of alcohol dependence. Methods Microarrays were used to measure changes in gene expression in peripheral blood in nonsmoking, social drinking subjects exposed to 3 types of personalized imagery: neutral, stressful (but not alcohol related), and alcohol‐related cues. Gene expression was measured at baseline, immediately after, and 1 hour after stimulus presentation. Subjects were allowed to drink up to 750 cc of beer in a “taste test” following stimulus presentation in each imagery condition, and the amount of beer consumed was recorded. Gene‐expression levels were compared in 2 groups of nonsmoking subjects (n = 11/group): heavy drinkers (HD; defined as regular alcohol use over the past year of at least 8 standard drinks per week for women and at least 15 standard drinks per week for men), and moderate drinkers (MD; defined as up to 7 standard drinks per week for women and 14 standard drinks per week for men). Expression of microRNA‐10a (miR‐10a) and microRNA‐21 (miR‐21) was assessed by quantitative real‐time polymerase chain reaction. Results After correction for multiple testing (false discovery rate < 0.05), 79 genes were identified that changed by >1.3‐fold in the HD group, but not the MD group, following exposure to stress. No changes were observed for any of these genes in either group following exposure to neutral or alcohol‐related imagery. Pathway analysis suggested that many of these genes, form part of the transactivation responsive (TAR)‐RNA‐binding protein (TRBP)‐associated complex and are positively regulated by miR‐10a and miR‐21. Expression of both miR‐10a and miR‐21 was up‐regulated following psychological stress in HD, but not MD subjects; however, the differences between groups were not statistically significant. Expression levels of both microRNAs was correlated (miR‐10a, R2 = 0.59, miR‐21 R2 = 0.57) with amount drunk in HD, but not MD subjects. Conclusions Expression of miR‐10a, miR‐21, and several of their target genes is regulated by acute psychological stress and is correlated with stress‐induced drinking in a laboratory setting. Alterations in miRNA expression may be one mechanism linking psychological stress with changes in gene expression and increased alcohol intake in binge/HD.